(untitled) (Fiep Bulletin - online, 2014)
Exist national and international references for the Physical Education that must be considered in the implantation of a curriculum to formation of teachers to this area. Objective: to verify if the universities that distribute the graduation in Physical Education Pedagogy in Chile, have the curriculum, indicated by the curricular structure of the courses, coherent with the Physical Education World Manifest, FIEP. Methodology: exploratory, documentary study; analysis of the dates from descriptive statistic. Sample: 33 universities that have the Physical Education Pedagogy course. Results: 84,84% of the structure of the courses have between 95,65 and 100% of coherence with the World Manifest of Physical Education – FIEP. It is possible to be concluded that the structure of the courses of the Chilean universities, for the Physical Education Pedagogy courses are, in its great majority, agreed with referring the international for the area of Physical education.